Estimating the Effect of Human Capital Spending on Unemployment in East Kalimantan Using the Chain Rule Method in Differentials - Dewi Mayarini Wulandari; Muhammad Anas (IECON: International Economics and Business Conference, 2023)
Unemployment is one of the development issues that arise as a result of the labor force growing faster than employment. Although the number of unemployed peoplein East Kalimantan Province has decreased, it is still quite high. The purpose of this studyis to estimate the direction and magnitude of the impact of human capital spending or expenditure on the Open Unemployment Rate in East Kalimantan Province from 2018 to 2020 using panel data regression with the Random Effects Model (REM) approach and the chain rule method. According to the findings of this study, education expenditure has a positive effect on average length of schooling (RLS), and health expenditure has a positive effect on life expectancy (UHH). The average length of schooling has a positive effect on the open unemployment rate in East Kalimantan province, while life expectancyhas no effect. Thus, mathematically, education expenditure has a positive effect on the open unemployment rate, proving the existence of a chain rule. Meanwhile, health expenditure has no effect on the Open Unemployment Rate, indicating that the chain ruleis invalid. The government is expected to be able to evaluate how the education and healthexpenditure budgets are being used in order to create superior human resources that are tailored to the needs of each region in East Kalimantan Province.